If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p = 2g + 2mforg Reorder the terms: p = 2fgmor + 2g Solving p = 2fgmor + 2g Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Simplifying p = 2fgmor + 2g
| 4x^2-2x-26=0 | | 2x+100=272 | | 6k-18=12-4k | | 2p-8=4-4p | | 2y+3(y-6)=7y-4(y-10) | | 2p-8=13-5n | | 2x-7/4+x=2x+7/2+5 | | 7-4a=5a-20 | | 2x+10=14+3x+3 | | 2x-7/4 | | 3n-27=13-5n | | 0.9x-14=1.7x-18 | | 2x+10=14+3 | | 10x+14=3(3x+4) | | 3n-9=13-5n | | 5x-7y=-9 | | 3x-16= | | -107x-7x=7x+19 | | 24x^2-47+20=0 | | x^2-7s=0 | | x^20-7s=0 | | (x-18)(x^2-36)=0 | | -6x^3-10x^2-6x=0 | | factorx^4+16= | | 12-4*(8-x)=20 | | x^4+16= | | 1/u+6=-6 | | -3(2s-3)-9=-2(7s+7)-2 | | x*y=1512 | | 10x-4x= | | 6timesx=4 | | 5(x-7)=40 |